Professional utilization in academic libraries a survey of eleven selected private colleges and universities in Metro Manila - Mallillin, Rogelio B. (1986)
The general objective of this study is to determine the librarians' role in selected colleges and universities within Metro Manila. Specifically, the study aimed to find out the professional and non-professional work involvement of 86 librarians, respondents to a questionnaire especially designed for the purpose. The ultimate objective was to see if some guidelines could be set in the assignment of clerical and professional work activities in academic libraries.